Parenting Anak Usia Dini dalam Perspektif Islam - Sisca Widyastuti (Universitas Al-Hikmah Indonesia, 2018)
This article discusses parenting in Islamic perspective. Parenting is a process of ongoing interaction between parents and their children which includes activities as follows: nourishing, guiding and protecting children as they grow. Being a parent is clearly a big affair, we are given by Allah SWT a great opportunity to build a small unit called family consisting of our spouse and children. This small unit that has important goals and challenges. The future will be continuous and hereditary framed by the successors of the family, namely children. Parents will guard the process of forming the children's future in their own ways. The children's vision and mission are arranged in parallel according to their age. And can not be separated from how parents guard him. A teacher is definitely a leader for his children in the world of education. While parents will take over the role if the child has returned home. Luqmanul Hakim in a stronger history, not a prophet. He is “just” a good man. In fact there is no valid history said, he was a slave, black, mediocre, pug nose, jet black skin. However, his name is immortalized by Allah, SWT. Became the name of one letter of prayer in Alqur'an, namely Luqman's letter. This paper wants to examine the messages of parenting in the Al-Qur'an Surat Luqman which are considered to represent the Islamic perspective in describing the concept of positive parenting early childhood.